Analyzing Bushing Model from Optimized Numerical Model Stiffness to Improve Vehicle Noise Performances - Kamaruzzaman, Amir Firdaus; Wan Abdul Rahman, Wan Mohd Wardi (Journal of Emerging Technologies and Industrial Applications, 2022)
Bushings material described as a hollow elastomer cylinder connected to the suspension system and vehicle chassis which act as strain energy potential where it dissipates energy between the components. The increased demand of the road safety and riding comfortability in a vehicle design makes noise levels an important parameter when producing new commercial vehicles. In this study, the idea of the optimized bushing stiffness where its numerical model is modified were proposed initially. The method is by optimizing the numerical model through MATLAB quadratic optimization programmed by the previous researcher which were designed and analyzed to make a comparative study to the initial proposed design through a series of static and frequency (natural frequency) analysis in the Solidworks 2020. This study shows when a force of 800kgf is applied in the static analysis, the optimized rubber bushing produced better results where the stress and strain distribution on the model looked more stable. This result is supported by the natural frequency analysis where optimized rubber bushing (model 2) produce better vibration frequency and achieved higher frequency of vibrations where its axial vibration was 553.13 Hz and torsional vibration of 608.76 Hz. When compared to the initial design (model 1) it was measured that its axial vibration produced 474.66 Hz and torsional vibration of 578.04 Hz. Hence, it shows the reliability of the optimized rubber bushing in terms of vibrations and deformation results. Bushing stiffness alterations is one of the reliable methods in terms of costing and time consumption as it is only required the modification of the rubber bushing material stiffness in comparison to the other method when working to reduce the vehicle noises and improve riding comfortability.